Down‐regulation of miR‐200b‐3p by low p73 contributes to the androgen‐independence of prostate cancer cells1. Issue 10 (6th February 2013) - He, Minyi; Liu, Yun; Deng, Xinjun; Qi, Songtao; Sun, Xuegang; Liu, Gang; Liu, Yongguang; Liu, Yawei; Zhao, Ming
Abstract BACKGROUND An increasing body of evidence indicates that microRNAs play critical roles in androgen‐independent prostate cancer (AIPC) growth. However, the regulation of the expression of microRNAs in AIPC is not very clear. In this study, we investigated the role that the interaction between miR‐200b‐3p and p73 plays in the proliferation of AIPC. METHODS We compared several relevant microRNAs and cancer related genes between the androgen‐dependent prostate cancer (ADPC) cell line and the AIPC cell line using quantitative real‐time PCR (Q‐PCR) and Western blot. Then we examined the effect of p73 and miR‐200b‐3p on the proliferation of AIPC and ADPC using CCK‐8. Furthermore we investigated the regulation of miR‐200b‐3p by p73. RESULTS p73 and miR‐200b‐3p were both downregulated in the PC3 cell line (AIPC). Down‐regulation of both p73 and miR‐200b‐3p increased the proliferation of ADPC cells cultured with androgen‐free medium, while up‐regulation of p73 and miR‐200b‐3p decreased the proliferation of AIPC cells. When p73 was over‐expressed in the AIPC cell subline, miR‐200b‐3p expression increased accordingly, while p73 was inhibited in ADPC cells cultured with androgen‐free medium and miR‐200b‐3p expression decreased significantly. CONCLUSION miR‐200b‐3p is down‐regulated by low expression of p73 in AIPC cells, and this interaction contributes to the proliferation of AIPC. Prostate 73: 1048–1056, 2013. © 2013 Wiley Periodicals, Inc.